Thermal Simulation of a Social Dwelling in Chile: Effect of the Thermal Zone and the Temperature-Dependant Thermophysical Properties of Light Envelope Materials - Ortega-Aguilera, R; Vasco-Calle, D (Elsevier Ltd, 2017)
As in most countries, Chile exhibits a continuous growth of energy demand, although nowadays the country does not have enough conventional energy sources to supply it. For this reason, energy saving approaches in the residential sector have been encouraged. One of the solutions to improve the energy performance of the buildings is to decrease wasting energy through the building s envelope, therefore the thermal properties of materials used in building envelopes must be analyzed to evaluate the thermal response of houses. Normally, the thermal envelope of a social house in Chile is made of brick or wood along with light materials such as fiber cement, plasterboard, and thermal insulating materials as polystyrene foam. The experimental part of this work deals with the measurement of the thermal conductivity and thermal diffusivity of the aforementioned light materials in a temperature range from −5 °C to 40 °C through the transient line heat source method. The experimental results allowed the identification of 10–20% variation of those thermophysical properties. The response of the thermal envelope and the inner temperature of a social dwelling under seven different climatological conditions was evaluated through transient simulations with EnergyPlus. The results allowed to identify that the dwellings located in hotter zones are prone to having higher temperatures than the comfort temperature, and the recommendations of the thermal regulations in Chile are more effective in the colder thermal zones 6 and 7. © 2016 Elsevier Ltd